Teaching Application of Economic Management Course based on Modern Information Technology - He, Yan; Xin, Hu; Yali, Peng (2021 International Conference on Internet, Education and Information Technology (IEIT), 2021)
Information technology is a kind of compound initiative element. Nowadays, people have generally affirmed the important position of information technology. As a powerful means, it has led education to a new revolution. In the current trend of rapid development of information technology, how to combine with education to improve the practical ability, application ability, independent ability and innovation ability of economic management talents has become the focus of all major education practitioners. Using the methods of literature research, document investigation and statistical analysis, this paper puts forward the key elements of the integrated application of information technology and economic management course from the theoretical and practical aspects, and systematically discusses the relationship between the methods, steps, implementation of information technology and the teaching purpose of the subject.